Survey of International Members of the American Thoracic Society on Climate Change and Health - Sarfaty, Mona (Ann Am Thorac Soc, 2016)
The American Thoracic Society (ATS), in collaboration with George Mason University, surveyed international members of the society to assess perceptions, clinical experiences, and preferred policy responses related to global climate change. A recruitment email was sent by the ATS President in October 2015 to 5,013 international members. Subsequently, four reminder emails were sent to nonrespondents. Responses were received from 489 members in 68 countries; the response rate was 9.8%. Half of respondents reported working in countries in Asia (25%) or Europe (25%), with the remainder in South America (18%), North America (Canada and Mexico) (18%), Australia or New Zealand (9%), and Africa (6%). Survey estimate confidence intervals were ± 5% or smaller. A high percentage of international ATS survey respondents judged that climate change is happening (96%), that it is driven by human activity (70%), and that it is relevant to patient care (“a great deal”/“a moderate amount”) (80%). A majority of respondents also indicated they are already observing health impacts of climate change among their patients; most commonly as increases in chronic disease severity from air pollution (88%), allergic symptoms from exposure to plants or mold (72%), and severe weather injuries (69%). An even larger majority anticipated seeing these climate-related health impacts in the next two decades. Respondents further indicated that physicians and physician organizations should play an active role in educating patients, the public, and policy makers on the human health effects of climate change. International ATS respondents, like their counterparts in the U.S., observed that human health is already adversely affected by climate change, and support responses to address this situation.